2009
DOI: 10.1016/j.virol.2009.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol biosynthesis modulation regulates dengue viral replication

Abstract: We performed a focused siRNA screen in an A549 dengue type 2 New Guinea C subgenomic replicon cell line (Rluc-replicon) that contains a Renilla luciferase cassette. We found that siRNA mediated knock down of mevalonate diphospho decarboxylase (MVD) inhibited viral replication of the Rluc-replicon and DEN-2 NGC live virus replication in A549 cells. When the Rluc-replicon A459 cells were grown in delipidated media the replicon expression was suppressed and MVD knock down could further sensitize Renilla expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
207
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(223 citation statements)
references
References 34 publications
9
207
0
Order By: Relevance
“…In addition, several studies on WNV have reported the cellular redistribution of cholesterol and its requirement for viral entry and replication (43,44). Finally, using DENV subgenomic luciferase replicon-expressing cell lines, treatment with various anti-cholesterol pharmacological drugs were shown to affect replication (45). These findings, along with those presented in this study, lead us to hypothesize that signaling through the ER via IRE1-JNK pathway might be important during the DENV life cycle.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, several studies on WNV have reported the cellular redistribution of cholesterol and its requirement for viral entry and replication (43,44). Finally, using DENV subgenomic luciferase replicon-expressing cell lines, treatment with various anti-cholesterol pharmacological drugs were shown to affect replication (45). These findings, along with those presented in this study, lead us to hypothesize that signaling through the ER via IRE1-JNK pathway might be important during the DENV life cycle.…”
Section: Discussionsupporting
confidence: 69%
“…Host kinases have been shown to be involved in DENV and WNV assembly and secretion (8,19). The cholesterol biosynthesis pathway has been linked to DENV entry and replication as well as to the host immune response (29,42). We recently showed that brequinar inhibits DENV through depletion of the intracellular level of pyrimidine (39).…”
mentioning
confidence: 99%
“…Lipid rafts consisting of sphingolipids and cholesterol and distributing to the outer leaflet of the cell membrane have been shown to be involved in the infection of not only many viruses but also several bacteria and parasites (24), in addition to playing roles in various functions such as lipid sorting, protein trafficking (26,47), cell polarity, and signal transduction (38). With respect to cholesterol itself, various aspects of the life cycle of flaviviruses have been shown to involve this lipid, including the entry of DENV (34), hepatitis C virus (HCV) (16), and WNV (27), the membrane fusion of tick-borne encephalitis virus (40), and the replication of HCV (14,17), WNV (23), and DENV (35). Recently Lee et al (20) showed that treatment with cholesterol efficiently impairs both the entry and replication steps of JEV and DENV-2 but enhances infection with the Sindbis virus (22).…”
mentioning
confidence: 99%